Road Spread Planning to Traffic Performance (Case Study: Roads Sukaraja, Jatiwangi, Majalengka) - Nurmala Dwiani; Yusra Aulia Sari (LEADER: Civil Engineering and Architecture Journal, 2024)
In the context of the growth of transportation infrastructure worldwide, the expansion of roads has become an important issue. Road expansion projects are often top priorities in various countries to overcome traffic congestion and improve interregional connectivity. Therefore, the role of the government in the construction of roads in Indonesia is crucial for sustainability and the need for infrastructure development and environmental protection. The purpose of the study paper entitled Road Enlargement Planning versus Traffic Performance is to investigate the effectiveness and impact of road enlargement as an infrastructure development strategy. The location of the research will be on Sukaraja Wetan Road in the Majalengka district. The quantitative method is used to observe the activity trend of Emperor Wetan. So, in this study, the survey was conducted directly at the place to be studied. The total LHR initial lifetime of the plan in 2025 with an initial traffic growth rate of 5% obtained is 1059. The amount of LHR end-life plan in 2035 with a final traffic growth figure of 7% obtaining is 1985. LEP and LEA calculations are obtained from the vehicle's distribution coefficient multiplied by the result of the initial LHR and the final LHR, then multiplied by the axis values on each vehicle. In both tables above, the LEP value is 101,746, while the LEA value is 190,6183. The LET value is 146,182, while the LER value is 148182. The CBR value is 4%, the Ground Support Force value is 4,289, and the Regional Factor is 2. The material plan to be used is the Laston Surface Layer, which is 7.5 cm, the Upper Foundation Layer (LPA) of Breakstone Class A is 20 cm, and the Lower Foundations Layer of Sirtu Class B is 40 cm.